2019
DOI: 10.1097/bpo.0000000000001052
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Pavlik Harness Treatment Regimens for Dislocated But Reducible (Ortolani+) Hips in Infantile Developmental Dysplasia of the Hip

Abstract: Level III-therapeutic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Developmental dysplasia of the hip refers to a spectrum of hip deformities, ranging from mild dysplasia to frank dislocation. In early-presenting infants, a Pavlik harness may solve the problem [1,2]. For those who failed the treatment or the early diagnosis, closed reduction (CR) or open reduction (OR) might be necessary within 24 months of age [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Developmental dysplasia of the hip refers to a spectrum of hip deformities, ranging from mild dysplasia to frank dislocation. In early-presenting infants, a Pavlik harness may solve the problem [1,2]. For those who failed the treatment or the early diagnosis, closed reduction (CR) or open reduction (OR) might be necessary within 24 months of age [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In total, 72% of respondents advise the harness to be worn for 24 hours a day when initiating treatment. Hines et al 8 recently suggested that neither reducing harness wear to 23 hours a day, nor reducing frequency of review, had an adverse effect on treatment success in Ortolani positive hips. Interestingly, of those who advise 23 hours a day, most have been in practice for less than five years, suggesting an awareness of current literature may trump ‘early years’ caution.…”
Section: Discussionmentioning
confidence: 99%
“…Very few comparative studies exist to inform the use of the Pavlik harness, 8,9 so it is unsurprising that there is little consensus among orthopaedic surgeons relating to the duration of use, or the timing and method of cessation. There is frequently discussion related to how many hours per day the harness is worn, if clothing is allowed beneath the harness, when treatment should be ceased and if it is stopped immediately or weaned.…”
Section: Introductionmentioning
confidence: 99%
“…In children that are tolerant and of suitable size, PH application is usually full time with one hour in the day for bathing/hygiene purposes. There is no difference between 23 and 24 h/day harnessing [65]. In children with Ortolani-positive hips, harnesses should not be removed by parents due to the risk of posterior wall erosion and higher failure rates [19].…”
Section: Part-time or Full-time Bracingmentioning
confidence: 99%